El buceo y las características lógicas de los mensajes prediseñados en el lenguaje no verbal en términos de las máximas conversacionales (2008)
ABSTRACT: Logical characteristics of predesigned messages in diving nonverbal code, in terms of conversational dicta, are discussed. This study consists of four basic steps —definition of interactional and transactional communication, a definition of predesigned messages, a presentation of speech acts of referring and preaching, logical characteristics of predesigned messages—, which are intended to determine how this language is made real.